ANTIFUNGAL ACTIVITY OF Cirsium arvense EXTRACTS AGAINST PHYTOPATHOGENIC FUNGUS Macrophomina phaseolina - BANARAS,S. (2017)
ABSTRACT Leaves, stems, roots and inflorescence of the asteraceous weed Circium arvense were extracted in methanol for two weeks. Methanol was evaporated in a rotary evaporator. Different concentrations (1, 2, 3, 4 and 5%) of methanolic extracts were prepared, and their antifungal activities were studied against Macrophomina phaseolina, using malt extract broth as growth medium. In general, extracts of all plant parts showed antifungal activities to variable extents. The highest antifungal activity occurred due to methanolic extract of leaves, followed by stem and root extracts, resulting in 10-74%, 6-57% and 11-39% reduction in fungal biomass over control, respectively. Inflorescence extract showed the least antifungal activity, resulting in 2-30% reduction in fungal biomass over control. There was a linear and inverse relationship between extract concentrations and fungal biomass for extracts of all the four parts. GC-MS analysis showed that there were 10 compounds in most effective methanolic leaf extract. Among these, 10-octadecanoic acid, methyl ester (26.442%), 2H-1-benzopyran, 6,7-dimethoxy-2-2-dimethyl (20.195%), hexadecanoic acid, methyl ester (15.752%) and 9,12-octadecadienoic acid (Z,Z)-, methyl ester (12.628%) were predominant compounds in the extract that may be responsible for antifungal activity. This study concludes that methanolic leaf extracts of C. arvense can be used for the management of M. phaseolina.